PROSES PEWARISAN TALE HAJI DALAM MASYARAKAT DESA KOTO MAJIDIN KECAMATAN AIR HANGAT KABUPATEN KERINCI - Syaiful Hayatunnufus; Syeilendra Syeilendra; Wimbrayardi Wimbrayardi (FBS Universitas Negeri Padang, 2013)
Abstract This research describes the endowment process of “Tale Haji” in the society of Desa Koto MajidinKecamatan Air Hangat Kabupaten Kerinci. The design of this research was the qualitative research by using the descriptive approach. The data were collected from literature reviews, observation, interview, and documentations. The data collected were then classified and analyzed by separating the primary data from the secondary. The findings of this research showed that the endowment process of “Tale Haji” was done in two forms of educations; the informal and the non formal. In the informal, the endowment process was done through families and the environment. Meanwhile, the non formal was done through an institution called as “Pusat Kegiatan Belajar Masyarakat” (PKBM) Koto Majidin. Kata Kunci: Tale Haji, Proses Pewarisan, Koto Majidin.